Impact of Work Discipline and Work Motivation on Employee Performance at Warehouse PT Shopee International Indonesia Branch Bekasi - Izzah, Nidaul; Septi Nugraheni (Yayasan Sinergi Kawula Muda, 2024)
This study aims to find out the impact of motivation and work discipline on the performance of employees of PT Shopee International Indonesia Branch of Bekasi. This is due to a discrepancy in the amount of stock found between the cycle count results and the data of the items in the system. Utilizing a quantitative research design, questionnaires were distributed to 160 participants, and IBM SPSS version 26 facilitated double linear regression analysis. The data's findings indicate that while work discipline has a negligible effect on employee performance, motivation has a partially favorable and considerable impact. A positive and significant influence of motivation and work discipline on the performance of employees at the Warehouse PT Shopee International Indonesia Branch of Bekasi is indicated by the F test results, which yielded a F count of 139.11 and a F table of 3.05, meaning the F count > F table with a Signification value of 0.00 < 0.05. The determination coefficient (R2) is 0.639, which indicates that 63.9% of employee performance is influenced by work discipline and motivation, with the remaining variables being determined by other factors that have not been investigated.